DESIGNING AND IMPLEMENTING DIGITAL MARKETING STRATEGY FOR AJF COLLECTION - Edy Yulianto Putra; Kelly Tan (ConCEPt - Conference on Community Engagement Project, 2022)
The spread of Covid-19 pandemic throughout the world, including Indonesia has caused most of the daily activities to be replaced by an online system. This causes the urgency for MSMEs to implement business marketing through a digital system. This study aims to create and implement the best business strategy in this current digital era for AJF Collection which is based in Batam, Indonesia. The strategy for this business is to create an e-brochure and start implementing digital marketing by using Instagram as the social media platform. The project started from September 2021 and was carried out until December 2021. Results of the study shows that e-brochure and implementation of digital marketing through Instagram has increased the user’s brand awareness towards AJF Collection’s products, which hold an important key in the business customer database growth.